2019
DOI: 10.1097/pcc.0000000000001825
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Catheter Size for Infants in Continuous Renal Replacement Therapy: Bigger Is Not Always Better*

Abstract: Objectives: Renal replacement therapy in infants and small children is the treatment of choice for severe oligoanuric renal dysfunction, with an increasing consensus that early initiation might contribute to preventing acute kidney injury complications. Safer renal replacement therapy devices specifically designed for neonates may contribute to ameliorating outcomes and increasing chances of survival. One of the crucial factors to achieve an effective renal replacement therapy in small infants is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This is true particularly for pediatric patients due to the younger age, the smaller vascular access available for CRRT, and the more limited blood flow achievable for extracorporeal treatment. Furthermore, considering that monitors specifically designed for pediatric treatment and characterized by miniaturized peristaltic pumps are not commonly available, periodic oscillations in the inflow line pressure may lead to excessively negative pressure and frequent treatment interruptions, ultimately causing circuit clotting [ 24 ]. For this reason, pharmacologic strategies for anticoagulation seem to be crucial in pediatric patients treated with CRRT to prevent this complication.…”
Section: Discussionmentioning
confidence: 99%
“…This is true particularly for pediatric patients due to the younger age, the smaller vascular access available for CRRT, and the more limited blood flow achievable for extracorporeal treatment. Furthermore, considering that monitors specifically designed for pediatric treatment and characterized by miniaturized peristaltic pumps are not commonly available, periodic oscillations in the inflow line pressure may lead to excessively negative pressure and frequent treatment interruptions, ultimately causing circuit clotting [ 24 ]. For this reason, pharmacologic strategies for anticoagulation seem to be crucial in pediatric patients treated with CRRT to prevent this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Larger‐diameter catheters, particularly greater than 10 French, also prolong circuit survival times 10 . However, a recent study by Garzotto et al found that 4 and 5 French catheters, commonly used in neonates, function best when hemodialysis pumps are proportional to catheter size 12 . All physical examination components leading to AV access have been illustrated in Table 1.…”
Section: Modalities Of Long‐term Vascular Accessmentioning
confidence: 99%
“…10 However, a recent study by Garzotto et al found that 4 and 5 French catheters, commonly used in neonates, function best when hemodialysis pumps are proportional to catheter size. 12 All physical examination components leading to AV access have been illustrated in Table 1. 10 Catheter size CVC size is based on the child's weight or age.…”
Section: Central Venous Cathetermentioning
confidence: 99%
See 1 more Smart Citation
“…Work by colleagues in Japan is focusing on a prototype machine that functions with as low as 3 to 5 mL of extracorporeal blood. These smaller circuits will require a more dedicated access point as demonstrated recently [22].…”
Section: Applications Of Crrtmentioning
confidence: 99%